Aktywność fizyczna i odżywianie w zdrowym stylu życia uczniów w wieku 10-13 lat ze Szkoły Podstawowej nr 9 w Inoworocławiu = Nutrition physical activity and healthy lifestyle in pupils aged 10-13 years of Primary School no 9 in Inoworocław - Niewiadomski, Tomasz; Napierała, Marek; Pezala, Małgorzata; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Niewiadomski Tomasz, Napierała Marek, Pezala Małgorzata, Zukow Walery. Aktywność fizyczna i odżywianie w zdrowym stylu życia uczniów w wieku 10-13 lat ze Szkoły Podstawowej nr 9 w Inoworocławiu = Nutrition physical activity and healthy lifestyle in pupils aged 10-13 years of Primary School no 9 in Inoworocław. Journal of Education, Health and Sport. 2015;5(6):355-374. ISSN 2391-8306. DOI 10.5281/zenodo.18713 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A355-374 https://pbn.nauka.gov.pl/works/567419 http://dx.doi.org/10.5281/zenodo.18713 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015. AKTYWNOŚĆ FIZYCZNA I ODŻYWIANIE W ZDROWYM STYLU ŻYCIA UCZNIÓW W WIEKU 10-13 LAT ZE SZKOŁY PODSTAWOWEJ NR 9 W INOWOROCŁAWIU NUTRITION PHYSICAL ACTIVITY AND HEALTHY LIFESTYLE IN PUPILS AGED 10-13 YEARS OF PRIMARY SCHOOL NO 9 IN INOWOROCŁAW Tomasz Niewiadomski1, Marek Napierała2, Małgorzata Pezala2, Walery Zukow2 1Wyższa Szkoła Gospodarki w Bydgoszczy 2Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: aktywność, odżywianie, zdrowy styl życia. Key words: activity, nutrition, healthy lifestyle. Streszczenie Niniejsze opracowanie dotyczy aktywności fizycznej i zdrowego odżywianie w zdrowym stylu życia. Celem pracy było zaprezentowanie czasu wolnego, aktywności fizycznej i odżywiania dzieci w wieku od 10 do 13 lat w Szkole Podstawowej nr 9 w Inowrocławiu. Praca składała się z dwóch części, teoretycznej i badawczej. Realizując temat postawiono następujące pytania badawcze: 1. Jak dzieci spędzają czas wolny? 2. Czy aktywność ruchowa odgrywa ważną rolę w życiu dzieci? 3. Czy dzieci rozumieją potrzebę zdrowego odżywiania? 4. Jaka jest samoocena sprawności fizycznej i zdrowia dzieci? Na podstawie pytań szczegółowych sformułowano hipotezę główną, która mówiła o tym iż aktywny tryb życia i zdrowe, racjonalne odżywianie pozytywnie wpływa na prawidłowy rozwój dzieci i młodzieży. Przy realizacji pracy zastosowano wiele metod badawczych. Wśród nich najważniejszą rolę odegrała ankieta, która dała realny obraz spędzania wolnego czasu i podejmowania aktywności fizycznej przez dzieci. Ankieta była anonimowa, a badaniami objęto grupę 60 osób. Opracowane następujące wnioski: 1. Dzieci dysponują znacznym czasem wolnym, którym nie potrafią prawidłowo dysonować. 2. Najczęściej podejmowaną formą spędzania czasu wolnego jest granie na komputerze bądź oglądanie telewizji. 3. Dzieci zdają sobie sprawę, z tego jak ważna jest aktywność fizyczna, jednak wybierają bierny tryb życia. 4. Dzieci najbardziej lubią jeździć na rowerze, a chłopcy grać w piłkę nożną. 5. Dzieci rozumieją potrzebę zdrowego odżywania i uprawianie sportu by wieść zdrowy tryb życia. Abstract The aim of the present study was to leisure time, physical activity and nutrition of children between the ages of 10 to 13 years in the Primary School No. 9 in Inowrocław. Work consisted of two parts, the theoretical and research. In pursuing erected on the following research questions: 1. How children spend their free time? 2. Does physical activity plays an important role in the lives of children? 3. Do the children understand the need for healthy eating? 4. What is the self-esteem of physical fitness and health of children? On the basis of detailed questions hypothesized principal, who spoke about this that an active lifestyle and a healthy, balanced diet positively affects the normal development of children and youth. In carrying the paper the multiple test methods. Among them, the most important role played by survey that gave a realistic picture of leisure and physical activity by children. The survey was anonymous, and research involved a group of 60 people. Developed following conclusions: 1. Children have substantial free time, which can not properly effects. 2. Most frequently undertaken a form of leisure is to play on the computer or watching TV. 3. Children are aware of how important physical activity, however, opt for passive lifestyle. 4. Children most like to ride a bike, and the boys play football. 5. Children understand the need for healthy nutrition and sport to live a healthy lifestyle.